Relationship between ANC Service Components (10 T) and Pregnancy Complications (Secondary Data from Demographic Survey) Indonesian Health 2017) - Indra Sulistiawati; Heriani Heriani (International Journal of Medicine and Health, 2024)
Globally, women dying from pregnancy complications decreased by almost 50% from 1990-2013, but the number of deaths remains high where 99% of deaths occur due to complications. Deaths caused by pregnancy complications cannot be avoided, but can be prevented through Antenatal Care (ANC) services as explained by previous studies that ANC services can reduce MMR by up to 20%. This study aims to determine the relationship between the 10T ANC Service Components and Pregnancy Complications. Quantitative research design with a cross-sectional approach. The population in this study were all Women of Childbearing Age (WUS) who gave birth to their last child in the last 5 years. Sample selection was determined based on the ratio using stratification and total sampling of 14,437. Bivariate analysis using the Chi-Square test and multivariate analysis using logistic regression. The results of the analysis showed that there were 2,539 (17.5%) women who experienced complications. Bivariate analysis showed a significant relationship between the components of ANC 10T services, education, wealth index, and residence with pregnancy complications, p- value <0.05, while parity showed no significant relationship with complications p = 0.378 . The results of multivariate analysis showed that women who did not receive the 10T service components according to standards had a 1,438 times higher risk of experiencing pregnancy complications after being controlled with the variables of parity, education, wealth index, and residence. This study provides important information for the next step in developing an ANC service strategy, namely providing services based on SOPs, improving skills and providing education to mothers and families about the importance of ANC services, in addition to policy making and increasing cooperation between stakeholders need to be done to optimize quality ANC services.